TINJAUAN YURIDIS KEBEBASAN PERS SSEBELUM dan SETELAH ERA REFORMASI BERDASARKAN PERATURAN PERUNDANG-UNDANGAN YANG BERLAKU - Ronny Andreas; Dodi Haryono; Abdul Ghafur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
During the New Order is a repressive regime, whereas in the era of reform after the Soeharto‟s fall press imposed by euphoria. During the New Order authoritarian make press system so consequently the press is curbed. In contrast, the Reformation reconanced as democratic future, including in terms of press freedom. The purpose of this research are: First, to explain the freedom of the press before the era of the Reformation by Act No. 21 of 1982 on the Principles of the Press and its amendment. Second, to explain the freedom of the press after the Reformation era by Act No. 40 of 1999 on the Press. Third, to explain the advantages and disadvantages of the press before and after the Reformation.From this research, there are three things that concluded. First, freedom of the press before the era of the Reformation by Act No. 21 of 1982 on the Principles of the Press and amendments if traced the articles are shackles for the life of the press, the press is required to issue a license issue this license that can be used to control the editorial contents and banning. Second, freedom of the press after the Reformation era by Act No. 40 of 1999 concerning the Press is to guarantee freedom of the press, because there is no silencing and banning. Third, before the Reformation era Indonesian press called Pancasila press with a free and responsible goals. However, there is no freedom, so no complaints as a result of the deviation of the freedom of the press. However, due to the strict control of the Government of the press lost their identity to carry out its functions independently.Freedom of the press after the Reformation era is done on a national responsibility without limitation license renewal. Disadvantages of the press after the Reformation era is freedom takes precedence over its responsibilities while the excess press after a press Reformation era became an independent institution. Suggestions writer, first to guarantee press freedom ideally built on a foundation of community interest media managers, and the interests of the target service. Secondly, with regard to the interests of community framework is advisable actualization national press freedom, not only will meet the interests unilaterally, either interest manager (source), and the top of the fulfillment of the target interest (public media). The press must be responsive to public situations, because the powerlessness of the public to appreciate his opinion to press leaders should act as a facilitator to be able to appreciate what is desired. Third, freedom of the press after the Reformation era should be retained but remained on its responsibilities so as not to be excessive.Keywords: Press, Before the Reformation, After Reform